Kajian Jejak Ekologis Kecamatan Mijen Kota Semarang Tahun 2016 - Sari Oktavia Dewi Nur Indah; Santoso Apik Budi; Hariyanto Hariyanto (Geo-Image, 2018)
Mijen subdistrict is one area that undergoing rapid development so that have impact to the carrying capacity of its region. The purpose of this study was to quantify the bio-ecological carrying capacity of Mijen Subdistrict through the study of the ecological footprint and biocapacity in 2016 and also projected the value in the 2031 by the projection of population. Data collection techniques that used are observation, image interpretation, questionnaires, secondary data and documentation. The value of the ecological footprint in 2016 is 0.456 gha/capita or 28,026.89 gha for the total value, and the biocapacity is 0.104 gha/capita or with total area of bioproductive lands 6,146.752 gha. The value of the deficit of the ecological footprint is 0.352 indicating the area entered the category of Minor Region. The value of the bio-ecological carrying capacity is 0.23, indicating the region have ecological deficit which means that ecosystems have been unable to support the demand of population. The projected value of ecological footprint in 2031 is 43.331,48 gha.